Studies on physical properties of fruits as indices of maturity in Lasora (Cordia dichotoma Forst 'F') (Indian Journal of Arid Horticulture, 2025)
Lasora (Cordia dichotoma Forst 'F') fruit is generally used as vegetable and for pickle making at home scale. It is an established fact that stage of maturity has a direct effect on the post harvest quality and storage life of the fruits. Early harvesting results in poor quality and uneven ripening, whereas delayed harvesting significantly reduces the shelf-life. In addition, stage of maturity influences the quality of the processed produce. Therefore, it is imperative that the fruits should be harvested at right stage of maturity.
Keywords: establish; Lasora (Cordia dichotoma Forst 'F'); ripening; harvesting